PELAGIC SEDIMENT, DEEP WATER CHEMISTRY, AND TECTONICS: AN APPLICATION OF THE HISTORY OF BIOLOGICAL SEDIMENT ACCUMULATION ON THE TECTONIC HISTORY OF THE CARIBBEAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
The distribution of biogenic silica in pelagic sediment enables us to demonstrate that the Central American isthmus shoaled from 35 to 15 MA, gradually stopping the transfer of dissolved silica in intermediate ocean water into the Caribbean. Between 15 and 4.2 MA it continued to shoal, but during this interval the effective transfer of silica had ceased. A barrier existed at 40 MA between the west Atlantic and the Caribbean, probably on the site of the present Lesser Antilles - Aves Ridge. This barrier prevented the transfer of silica to the western Atlantic at the time of the removal of Atlantic intermediate and deep water silica by the newly formed North Atlantic Deep Water (NADW). The barrier was breached at about 19 MA, enabling silica from the Caribbean to penetrate at least to a few hundred km east of the Lesser Antilles (Site 543 DSDP).
Keywords: Pelagic sediment; Biogenic silica; Central American isthmus; Tectonic history